Concrete for Resilient Infrastructure: Review of Benefits, Challenges and Solutions - Janev, Dejan; Nakov, Darko; Arangjelovski, Toni (Macedonian Association of Structural Engineers (MASE), 2023)
Given the persistent and far-reaching impact of climate change on our global community, we must design our infrastructure to withstand the effects of this phenomenon. These effects may manifest in extreme weather patterns such as temperature changes, rising sea levels, powerful winds and storms, and natural disasters. Therefore, we must prioritize developing resilient infrastructure that offers benefits such as public safety, reduced economic losses, and continuity of critical services. Concrete gains wide recognition due to its robustness, durability, longevity, strength, and safety attributes. These qualities make it an ideal material to enhance structures' resiliency and adaptive capacity in response to climate-related and natural disasters. Concrete structures are more resistant to extreme conditions and catastrophic events than other building materials, such as wood and steel. The impact of climate change on concrete structures is a growing concern, with extreme weather events and rising sea levels accelerating concrete degradation. Unfortunately, cement production is a significant contributor to carbon dioxide emissions, accounting for approximately 5-10% of global carbon emissions. One way to address this issue is by utilizing Limestone Calcined Clay Cement (LC3) types, and incorporating cement substitutes such as fly ash and slag to reduce the carbon footprint. Another significant concern is the corrosion of reinforcement within concrete structures, commonly caused by chloride ingress and carbonation. Chloride ions from sources like deicing salts and seawater penetrate the concrete and initiate corrosion in the reinforcement. Carbonation, caused by exposure to carbon dioxide, reduces concrete alkalinity, further promoting corrosion. Several effective measures are available to enhance the durability of concrete and prevent reinforcement corrosion, including utilizing materials with corrosion-resistant properties, applying protective coatings, integrating corrosion inhibitors, creating low-permeability concrete mixtures, and adhering to appropriate construction practices. Concrete's strength, durability, and adaptability make it indispensable for building resilient structures. However, climate change and reinforcement corrosion present challenges. Embracing sustainable cement alternatives like LC3 and implementing preventive measures can enhance concrete resistance, extend structure longevity, and ensure resilience in the face of future challenges.
Keywords: concrete; resilient structures; climate change; durability; corrosion